The Ark of shared value : using shared value creation to increase corporate social responsibility investments - Saenz, Cesar (Emerald Publishing Limited, 2024)
The Ark of Shared Value is a fundamental guide for those involved in designing and implementing sustainable business projects. The Ark is a one-page tool that is easy to use and presents the key elements of sustainable projects. This tool incorporates visual thinking for sustainable projects, allowing designers to discuss and collaborate on the project effectively. Cesar Saenz offers the Ark of Shared Value as a tangible way to present sustainable projects, including the stakeholders involved, resources used, activities conducted, and benefits received for each stakeholder, all on a single page. Companies and organizations, as well as professionals who believe that doing business can enhance the environment and social well-being, can utilize The Ark of Shared Value.
Includes index.
Keywords: Business ethics.; Teams in the workplace.; Business & Economics -- Business Ethics.; Business ethics and social responsibility.; elektronické knihy; electronic books